Unified framework for analysis and design optimization of a multirotor unmanned aerial vehicle - Lim, D.; Kim, H.; Lee, B.; Yee, K. (My University, 2018)
Designing a small-scale multirotor UAV is a complicated procedure that requires multi-disciplinary analyses including rotor aerodynamics, structure, and electric propulsion system. However, owing to the complexity of multi-disciplinary analyses, the design of conventional multirotor UAVs heavily relies on the empirical methods through experimental data or legacy selections. These methods not only lack the firm physical basis for selecting the component, but also are extremely time-inefficient, requiring numerously repetitive experiments. In order to establish a systematic design procedure for multirotor UAVs, the unified design optimization framework, titled as Conceptual Layout Optimization for Universal Drone Systems (CLOUDS), was developed in this study. CLOUDS consists of five multi-disciplinary analysis modules including aerodynamics and electric propulsion system. Utilizing these modules, it can accurately estimate the performance of the system in response to the variation of the combination of components, showing high accuracy of predicting the flight time within 10% deviation. As such, the optimal configuration of multirotors could be designed for a specific mission. Based on the developed framework, correlations between the variables are found using Self-Organizing Maps (SOM) and Analysis of Variance (ANOVA). Additionally, design optimizations were conducted for two hover missions with different time as an example. The optimum design solution was presented by analyzing the optimization results.